Performance and selectivity of cationic nanoparticle pseudo‐stationary phases in electrokinetic chromatography. Issue 5 (20th December 2016) - McGettrick, Julie R.; Williamson, Nathan H.; Sutton, Adam T.; Palmer, Christopher P.
Abstract : Electrokinetic chromatography (EKC) is a powerful analytical technique that uses an ionic pseudo‐stationary phase (PSP) to separate neutral compounds. Although anionic surfactants are the most common choice for PSP, cationic latex nanoparticles are an attractive alternative. Reversible addition‐fragmentation chain transfer (RAFT) polymerization was used to synthesize several types of diblock copolymers that self‐assemble into latex nanoparticles, which were characterized by a variety of techniques including diffusion NMR. The performance of each nanoparticle as a PSP was studied by using a homologous series of ketones and linear solvation energy relationships (LSER) analysis. A cationic homopolymer coating was found to be necessary to prevent band broadening caused by analyte interactions with nanoparticles adsorbed to the capillary surface. No significant difference in methylene selectivity or LSER parameters was observed between nanoparticles with different cationic shells, but differences were observed between nanoparticles with different hydrophobic cores. Cationic latex nanoparticles behaved more like anionic latex nanoparticles than like cationic surfactants, suggesting that selectivity is primarily driven by the hydrophobic portion of a PSP. Cationic latex nanoparticles in combination with a homopolymer cationic capillary coating are an excellent choice for EKC analyses where an anodic electroosmotic flow is required.